Analisis Hubungan Antara Kesejahteraan Karyawan dan Kinerja Karyawan pada Divisi S & U di PT. R I (Unit K B) - Siti Maisyaroh; Aniska Putri; Naelli Rodianah Qolbiy; Doni Teguh Wibowo (Jurnal Bisnis Islam dan Kewirausahaan, 2025)
This study aims to analyze the relationship between employee welfare and employee performance at PT. R I (Unit K B), S & U Affairs. Using a quantitative approach with a survey design, data were collected from 30 employees through a questionnaire that measures aspects of physical, mental, financial, and social well-being, as well as employee performance including quality, quantity, efficiency, and work attitude. Descriptive analysis shows that the majority of employees have a positive perception of their well-being, but there are several areas that require further attention. Inferential analysis, especially the Spearman correlation test, shows a significant positive relationship between employee well-being and employee performance. The results of this study confirm the importance of employee well-being as a critical factor that has a significant impact on performance, and provide insight for companies in improving employee well-being and productivity